Numerical modeling of co-emissions for gas turbine combustors operating at part-load conditions. (6th July 2018) - Klarmann, Noah; Zoller, Benjamin Timo; Sattelmayer, Thomas
Abstract : A numerical model is presented for the precise prediction of carbon monoxide (CO) emissions in gas turbine combustors. All models are based on Computational Fluid Dynamics (CFD). This work starts with an introduction of fundamental mechanisms, which are responsible for CO emissions. As we will show, there is a need of CO-models as standard combustion models fail to predict CO-emissions precisely. For the purpose of validation, experiments are conducted. High ratios of secondary air is bypassing the burner in order to induce interaction of the flame front with secondary air, as the flame brush gets diluted and decreases in reactivity. Note, this is an important mechanism for elevated CO emissions in multi-burner systems with high staging ratio. Five operating points with each having a different adiabatic flame temperature were measured. They include equilibrium (complete burnout) and superequilibrium CO (incomplete burnout). In summary, it is shown that the prediction of CO with the presented models lead to a significant improvement as it captures the transition from equilibrium to superequilibrium CO. Furthermore, the strong underestimation of CO predicted by standard combustion models is shown.